PROSES PEMBERSIHAN SYNGAS HASIL GASIFIKASI TEMPURUNG KEMIRI MENGGUNAKAN SIKLON - Jemseng Carles Abineno; Johny Agustinus Koylal (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
This study aims to examine the process of cleaning for synthesis gas (syngas) resulted from candlenut shell gasification by using a cyclone. Research was started by design or manufacture a cyclone as a tool that can condense the tar carried in the syngas produced from the gasification process. This tool was tested with by trial and error such that got a tool that can function optimally to condense tar. The syngas cleaning experiment using the cyclone was conducted by four treatments, namely S1 (1 cyclone), S2 (2 cyclones), S3 (3 cyclones), and S4 (4 cyclones).  All treatments were repeated 4 (four) times, so there were 16 experimental units. The parameter measured is the amount of tar that was condensed on the cyclone. Result showed that the syngas cleaning process using a cyclone worked well, and the best treatment was S3 (3 cyclones) with an average amount of condensed tar of 141.7 ml/kg of shell. The use of cyclones can condense tar and other particulates carried in the syngas. The cleaned syngas can be applied as fuel in an internal  combustion engine as a substitute for diesel and gasoline fuels.       Keywords: gasification, syngas, cleaning, cyclone